2020
DOI: 10.1016/j.jhazmat.2019.121665
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mercury in sediments, plant and animal tissues in Matang Mangrove Forest Reserve, Malaysia

Abstract: Charcoal production activities at the Matang Mangrove Forest Reserve (MMFR) in Peninsular Malaysia have a potential to emit volatile compounds such as Hg back into the ambient environment, raising concerns on the public health and safety. The present study was aimed at analyzing Hg concentration from different plant/ animal tissues and sediment samples (in total 786 samples) to understand clearly the Hg distribution at the MMFR. Leaves of Rhizophora spp. showed higher Hg concentration with an increasing trend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 60 publications
0
7
0
1
Order By: Relevance
“…The potential data on mangrove density showed that the mangrove ecosystem in Muara Kali Ijo is regenerating (Hilmi et al 2015;Nur and Hilmi 2021). Mangrove density, domination, and regeneration of mangrove species have a positive impact on the potentials of plankton (Andriyani et al 2020;Hilmi et al 2020), other micro and macro-organisms (Su et al 2012;Yin et al 2018), land animal habitats, other organisms, and birds (Putra et al 2019;Wolswijk et al 2020).…”
Section: Mangrove Densitymentioning
confidence: 99%
“…The potential data on mangrove density showed that the mangrove ecosystem in Muara Kali Ijo is regenerating (Hilmi et al 2015;Nur and Hilmi 2021). Mangrove density, domination, and regeneration of mangrove species have a positive impact on the potentials of plankton (Andriyani et al 2020;Hilmi et al 2020), other micro and macro-organisms (Su et al 2012;Yin et al 2018), land animal habitats, other organisms, and birds (Putra et al 2019;Wolswijk et al 2020).…”
Section: Mangrove Densitymentioning
confidence: 99%
“…The potential mercury contaminants comes from the oil and cement industry, garbage, and household 3,5 . The mangrove stand has a specific metabolism system, specific nutrient absorption and specific root activity 3,5,6 . In Eastern Segara Anakan, the mangrove stand has a specific freshwater supply from Sapuregel, Donan and Kembang Kuning Rivers 4, 7-10 and seawater from Samundra, Indian Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…The adaptation pattern of mangrove vegetation to grow and survive in the polluted area can be conducted by the activity of speci c root and metabolism system (Hilmi et al 2017b, a). This activities can be used to reduce impact of heavy metal contaminant following nutrient absorption activity (Hilmi et al 2017b, a; Wolswijk et al 2020).…”
Section: Introductionmentioning
confidence: 99%